Factors Influencing the Adoption of IoT for E-Learning in Higher Educational Institutes in Developing Countries - Madni, Syed Hamid Hussain; Ali, Javed; Husnain, Hafiz Ali; Masum, Maidul Hasan; Mustafa, Saad; Shuja, Junaid; Maray, Mohammed; Hosseini, Samira (Frontiers in Psychology, 2022)
The Internet of Things (IoT) is an emerging paradigm of educational applications and innovative technology in the current era. While capabilities are increasing day by day, there are still many limitations and challenges for utilizing these technologies within E-Learning in Higher Educational Institutes (HEIs). IoT is well implemented in the United States of America (USA), United Kingdom (UK), Japan, and China but not in developing countries, including Saudi Arabia, Malaysia, Pakistan, Bangladesh, etc. Few studies have investigated the adoption of IoT in E-Learning within developing countries. Therefore, this research aims to examine the factors influencing IoT adoption for E-Learning to be utilized in HEIs. Further, an adoption model is proposed for IoT based E-Learning in developing countries contexts and provides recommendations for enhancing the IoT adoption for E-Learning in HEIs. The IoT based E-Learning model categorizes these influencing factors into four groups: individual, organizational, environmental, and technological. Influencing factors are compared along with a detailed description in order to determine which factors should be prioritized for efficient IoT based E-Learning in HEIs. We identify the privacy (27%), infrastructure readiness (24%), financial constraints (24%), ease of use (20%), support of faculty (18%), interaction (15%), attitude (14%), and network and data security (14%), as the significant E-Learning influencing factors on IoT adoption in HEIs. These findings from the researcher’s perspective will show that the national culture has a significant role and conclude the individual, organizational, technological, and environmental behaviour towards using new technology in developing countries.